The Influence of Diabetic Foot Exercises on the Risk of Diabetic Ulcers in Patients with Diabetes Mellitus - Endang Purwaningsih; Heru Wiratmoko; Agus Wiwit Suwanto (Health and Technology Journal (HTechJ), 2024)
Diabetes Mellitus is a non-communicable disease that continues to experience an increase in the number of cases with high mortality and morbidity rates, expected to triple by the year 2030. In the long term, it can lead to microvascular, macrovascular, and neuropathic complications such as peripheral vascular disease, indicating abnormalities in the lower limbs, manifested as diabetic ulcers. The research aims to determine the Influence of Diabetic Foot Exercises on the Risk of Diabetic Ulcers in Patients with Diabetes Mellitus at Sukosari Community Health Center in Babadan Subdistrict, Ponorogo Regency. The research design is a pre-experimental study with a One Group Pretest-Posttest approach. The study was conducted from June to August 2023. The population consisted of all Diabetes Mellitus patients at Sukosari Community Health Center in Babadan.  Sample of 30 respondents was selected using purposive sampling. The independent variable was the risk of diabetic ulcers, and the dependent variable was diabetic foot exercises. The observation instrument used was Inlow's 60-second diabetic foot screening tool. Statistical analysis was performed using the Wilcoxon signed-rank test through SPSS with α = 0.05. The research results showed that the risk of diabetic ulcers before diabetic foot exercises, more than half of the respondents (63.3%), had a moderate category, and 43.3% had a mild category. There is an influence of Diabetic Foot Exercises on the Risk of Diabetic Ulcers in Patients with Diabetes Mellitus at Sukosari Community Health Center in Babadan Subdistrict, Ponorogo Regency, with a p-value of 0.000 ≤ α 0.05. Diabetic foot exercises can be performed independently, without the need for equipment, and at no cost. It is hoped that patients with Diabetes Mellitus can perform them regularly, systematically, and continuously, with the expectation of reducing the risk of diabetic ulcers.